2012 Asia-Pacific Symposium on Electromagnetic Compatibility 2012
DOI: 10.1109/apemc.2012.6237807
|View full text |Cite
|
Sign up to set email alerts
|

EMI suppression for single-phase grid-connected inverter based on chaotic SPWM control

Abstract: Ahstract-This paper is to design a novel chaotic sinusoidal pulse width modulation (SPWM) for grid-connected inverters, which has the advantages in design flexibilities and low costs, for reducing electromagnetic interference (EMI). Furthermore, the proposed chaotic SPWM can also be used to improve the total harmonic distortions (THD) of grid-connected currents without excessive harmonics. Here, a chaotic carrier is the key to realize the chaotic SPWM control. Finally, simulation and experimental results are g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Thus, it can be concluded that the proposed scheme can be used for attaining EMC where conducted noise reduction attained is less than 4 dB. In addition, the proposed scheme reduces the size of the EMI filter required [22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it can be concluded that the proposed scheme can be used for attaining EMC where conducted noise reduction attained is less than 4 dB. In addition, the proposed scheme reduces the size of the EMI filter required [22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…The authors in [105], [106] implemented the technique that involves the use of the chaotic sinusoidal pulse width modulation (CSPWM). Here, the methodology depends on a chaotic carrier as it is the key to realize the chaotic SPWM control.…”
Section: Concept Of Random Carrier Frequency Modulationmentioning
confidence: 99%